2015
DOI: 10.3390/md13085128
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids from Marine Microalgae: A Valuable Natural Source for the Prevention of Chronic Diseases

Abstract: Epidemiological studies have shown a relation between antioxidants and the prevention of several chronic diseases. Microalgae are a potential novel source of bioactive molecules, including a wide range of different carotenoids that can be used as nutraceuticals, food supplements and novel food products. The objective of this review is (i) to update the research that has been carried out on the most known carotenoids produced by marine microalgae, including reporting on their high potentialities to produce othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
102
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(104 citation statements)
references
References 166 publications
(195 reference statements)
1
102
0
1
Order By: Relevance
“…Among the bioactive compounds, carotenoids are natural pigments present in vegetables and fruits which are used as food additives and possess important physiological properties. They are also excellent antioxidants, as they are precursors of vitamin A. Epidemiological studies have associated the consumption of foods plentiful in bioactive compounds with reduced risk of developing chronic diseases . A subgroup of flavonoids, the anthocyanidins comprises the red/blue pigments found in fruits and flowers that have high bioactivity such as antioxidant effects .…”
Section: Introductionmentioning
confidence: 99%
“…Among the bioactive compounds, carotenoids are natural pigments present in vegetables and fruits which are used as food additives and possess important physiological properties. They are also excellent antioxidants, as they are precursors of vitamin A. Epidemiological studies have associated the consumption of foods plentiful in bioactive compounds with reduced risk of developing chronic diseases . A subgroup of flavonoids, the anthocyanidins comprises the red/blue pigments found in fruits and flowers that have high bioactivity such as antioxidant effects .…”
Section: Introductionmentioning
confidence: 99%
“…Many biological and therapeutic functions of cordycepin such as antitumor, antimetastatic, antibacterial, antiviral, immunomodulatory and anti‐inflammatory have been studied and confirmed (Ahn, Park, Lee, Shin, & Choi, 2000; Jeong et al, 2010; Jeong, Jin, et al, 2012; Jeong, Seo, et al, 2012; Kim et al, 2006; Kodama, McCaffrey, Yusa, & Mitsuya, 2000; Lee, Moon, June, Kim, & Moon, 2010). Carotenoids have been widely used in health care products, pharmaceuticals, cosmetics and other fields due to their proven health benefits (Raposo, De Morais, & De Morais, ; Wang, Manabe, Sugawara, Paul, & Zhao, ). The orange color of the fruiting body of C. militaris is caused by the carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…It is an α-hydroxyketocarotenoid with potent antioxidant activity both in vitro and in vivo [2,3,4,5,6,7], and its radical scavenging activity has been shown to be higher than that of other carotenoids and vitamin E [2,3,4]. Goto et al suggested that the molecule’s conjugated polyene and terminal moieties trapped radicals in the phospholipid membrane and at the surface (Figure 1) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Goto et al suggested that the molecule’s conjugated polyene and terminal moieties trapped radicals in the phospholipid membrane and at the surface (Figure 1) [5]. Astaxanthin from H. pluvialis exhibits high bioavailability [2,6,7]. Therefore, although astaxanthin is a non-provitamin A carotenoid, it would be expected to help prevent lifestyle-related diseases by reducing oxidative stress and chronic inflammation [2,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation